Public Procurement And Project Management At Transitional Context : Analysis Of Single Source Contracting Practices - Bhatta, Jayendra Prasad; Sain, Manoj (A Bi-annual South Asian Journal of Research & Innovation, 2023)
Procurement of goods, works and services are considered as key functions of every government to achieve their development strategy goals which consumes the large amount of national GDP and annual budget. Public procurement shall be carried out in a transparent, accountable, effective, competitive and efficient manners with high level of integrity. Procurement and contracting operations using single-source or direct contracting method (an alternative to competitive options) creates a lot of controversies. The aim of this study is to explore the issues and practices of single source procurement and contracting methods, their justifications and impact on the project performance and sustainability. Adopting the mixed approach of qualitative and content analysis techniques; case study of conflict effected nations is conducted. For this purpose, a systematic literature review (SLR) of 15 conflict affected nations in Asia is carried out and case study of Timor-Leste located in East-Asia and Nepal located in South-Asia is conducted on the basis of research purposive approach. Similarly, a group discussion, preliminary interviews and in-depth interviews are also conducted involving project stake holders and then simple triangulation approach is applied for verification and validation purpose. Findings from in-depth interviews of 30 experienced participants, 5 group discussions and 10 preliminary interviews are included in this research paper. The participants have identified 15 key factors those are responsible for single-source contracting decisions like poor institutional capacity, political interference, corruption motives, weak private sector competition, decision delays, collusions among bidders, emergency situations and others. Identified consequences of direct contracting methods are delivery of goods and services in poor quality, cost overrun, promote corruption, social conflict, injustice, political instability including overall projects performance. It is expected that the findings of this research will contribute to a better understanding towards proper application of the available competitive methods of public procurement and contracting operations rather than selecting the non-competitive choices.